Which adenomas are detected by fecal occult blood testing?: a state-wide analysis from Bavaria, Germany - Brenner, Hermann; Hoffmeister, Michael; Birkner, Berndt; Stock, Christian (International journal of cancer, 2015)
Guaiac-based fecal occult blood tests (gFOBTs) are the most widely used noninvasive tests for colorectal cancer screening. While it is well known that they detect only a minority of colorectal adenomas, evidence for the characteristics of adenomas associated with detection is sparse. We derived estimates of the positive likelihood ratio (LR+), a summary measure of diagnostic performance, according to adenoma characteristics by comparing findings at colonoscopy among 19,208 and 181,128 participants who underwent colonoscopy to follow-up a positive gFOBT and as a primary screening examination, respectively, in Bavaria, Germany, in 2007-2009. Age and sex-adjusted estimates of LR+ (95% confidence intervals, 95% CI) ranged from 1.09 (1.05-1.13) for adenomas <1 cm to 2.52 (2.30-2.75) for adenomas >2 cm, and were much higher for pedunculated adenomas (1.96, 95% CI 1.85-2.08) than for flat or sessile adenomas (1.11, 95% CI 1.02-1.21 and 1.12, 95% CI 1.08-1.16, respectively). Villous or tubulovillous structure and dysplasia were likewise associated with a higher chance to be detected by gFOBT. Diagnostic performance was worse for proximal than for distal adenomas (age and sex adjusted LR+:1.16, 95% CI 1.09-1.23 and 1.35, 95% CI 1.29-1.41, respectively) which was explained by the lower proportions of large, pedunculated and nontubular adenomas in the proximal colon. Size, pedunculated shape, and nontubular histology are the key determinants of detection which also explain lower detection rates of adenomas located in the proximal colon.